1975
DOI: 10.1042/bj1470425
|View full text |Cite
|
Sign up to set email alerts
|

An allosteric model for ribonuclease.

Abstract: Data from two assay systems show that the kinetics of the hydrolysis of cytidine 2': 3'-cyclic monophosphate by bovine pancreatic RNAase (ribonuclease) is not consistent with conventional models. An allosteric model involving a substrate-dependent change in the equilibrium between two enzyme conformations is proposed. Such a model gives rise to a calculated curve ofvelocity versus substrate concentration which fits the experimental data. The model is also consistent with the results of an examination of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

1978
1978
1998
1998

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…At relatively low concentrations of this type of substrate, in an aqueous environment, the only significant route is that of hydrolysis, and a hyperbolic substrate concentration dependence is usually obtained. However, working at high substrate concentrations, Walker et al (4,5) observed that at pH 7.0, the dependence of the rate of hydrolysis with substrate concentration shows a nonhyperbolic behavior: there is a drop at about 25 mM to 30 mM CϾp 1 followed by a second rise and then a gradual decline, which they interpreted by an allosteric model in which there is a substrate-dependent change in the equilibrium between three pre-existing enzyme conformations, one of which inactive. Later, Piccoli and d'Alessio (6) also showed deviations from hyperbolic kinetics for RNase A with CϾp, but only at a low substrate concentration.…”
mentioning
confidence: 99%
“…At relatively low concentrations of this type of substrate, in an aqueous environment, the only significant route is that of hydrolysis, and a hyperbolic substrate concentration dependence is usually obtained. However, working at high substrate concentrations, Walker et al (4,5) observed that at pH 7.0, the dependence of the rate of hydrolysis with substrate concentration shows a nonhyperbolic behavior: there is a drop at about 25 mM to 30 mM CϾp 1 followed by a second rise and then a gradual decline, which they interpreted by an allosteric model in which there is a substrate-dependent change in the equilibrium between three pre-existing enzyme conformations, one of which inactive. Later, Piccoli and d'Alessio (6) also showed deviations from hyperbolic kinetics for RNase A with CϾp, but only at a low substrate concentration.…”
mentioning
confidence: 99%
“…They are ribonucleotide triphosphate reductase (26-28), pancreatic ribonuclease (29)(30)(31), and wheat hexokinase Ll (32). In all these cases there are evidences that the enzymes are single polypeptide chains, but unequivocal proof that they do not oligomerize during the assay has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Walker et al, 1975(Walker et al, , 1976) have demonstrated that conditions that favour the binding of ligands to the allosteric sites (e.g. increased concentrations of the substrate or its analogues) favour a shift in the equilibrium towards form F of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Activity was measured at pH 7.13 and 10.3, unless otherwise specified, by using the pH-stat assay described by Walker et al (1975 the pH of the assay system is increased, [Sm] remains constant below pH 8.5 and above pH 10, but increases between these values, reflecting the titration curve for lysine side chains (see Table 1). The slope of the Vol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation